Correlation Of Level Anxiety With Decreased Appetite In Breast Cancer Patients Who Perform Chemotherapy In Edelwis Room Ulin Hospital Banjarmasin - Rifa’atul Mahmudah; Umi Hanik Fetriyah; Muhammad Jamaludin (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2018)
Background: Breast cancer is one cause of death for women. Patients with breast cancer should undergo chemotherapy and chemotherapy treatment may lead to decreased appetite due to chemotherapy substances resulting in increased stomach acid so that patients often experience nausea vomiting resulting in a lack of nutritional intake.Objective: Annalyze Correlation of anxiety levels with decreased appetite in breast cancer patients who perform chemotherapy in Edelwis Room Ulin Hospital Banjarmasin.Method: This type of research used an analytical survey with cross sectional approach. Thepopulation is 121 people who perform chemotherapy in Edelwis Room Ulin Hospital Banjarmasin. The sample in this study is part of the population taken using accidental sampling technique amounted to 30 people who perform chemotherapy in Edelwis Room Ulin Hospital Banjarmasin. Data werecollected using questionnaire method by using Gamma correlation test with significance level 95% (α= 0,05).Result: Most of the respondents were 35 years old (81.8%), high school level as many as 29 people(52.7%), the duration of chemotherapy for 1 year was 25 people (45.5%), Has a severe anxiety levelwith a decrease in appetite weight as much as 16 people (29.1%) and most of the respondents havedecreased appetite weight as much as 114 people (65.5%). The result of analysis with Gamma coefficient test obtained the result that p value = 0,009.Conclusion: There is an anxiety level relationship with decreased appetite in breast cancer patients who perform chemotherapy in Edelwis Room Ulin Hospital Banjarmasin.Keywords: Anxiety, Breast Cancer, Appetite,